A systematic literature review of the vehicle routing problem in reverse logistics operations. (March 2023) - Sar, Kubra; Ghadimi, Pezhman
Highlights: This paper reviews the VRP studies in the RLs domain between 2000 and 2022. Hybrid and approximate solution methods are preferred rather than exact solution techniques. Some types of waste, such as medical waste, are ignored by previous researchers. Research gaps and future study opportunities are highlighted. Abstract: The increasing rate at which goods ranging from food products to electronic products are consumed has led to rapidly increasing waste worldwide. This huge amount of waste poses an environmental threat but can have economic value. Thus, governments argue that this waste should be collected and included in recycling processes. However, collecting these wastes can pose some logistical problems, such as the large amounts of carbon emissions created and the need for transportation plans to collect these costly wastes. Many researchers and industrial practitioners have developed vehicle routing systems for reverse logistics operations to address and model these logistical challenges. To date, few efforts have been made to systematically review vehicle routing models in the reverse logistics process. This paper provides a literature review of 109 published articles in international scientific journals related to the vehicle routing problem in the reverse logistics domain between 2000 and 2022. Six carefully designed questions are proposed and answered in this article regarding modelling approaches, solution techniques, vehicle routing problem variants, sustainability aspects, waste types, and future research opportunities. According to the results of the review, some important points were highlighted and discussed.